The Facilities of Badminton Field in West Sumatera - Sepdanius, Endang (International Journal of Scientific Research and Management (IJSRM), 2021)
This study aims to reveal the suitability of badminton field facilities in West Sumatera based on badminton regulatory indicators. The criteria used are the criteria issued by the Badminton game rules of the World Federation. The method in this research uses quantitative methods with a descriptive approach. Data were collected by conducting direct observations in the field and interviews with field owners. The results of the research were that 78% of the field meets the criteria related to the width of the field line, 81% was related to the height of the pole, 73% was related to the depth of the net, 78% was related to the width of the net, 71% was related to the net height in the middle of the field, 79% was related to the net height at double pile area, 34% related to no gap between the netting and the netting posts, 90% to the length of the court, 86% was related to the width of the doubles court, 77% to the width of the single court, 75% to the net distance to the short service line, 79% to the long service area of ​​the singles. Information from interviews found that carpet-based fields met the requirements of the field because they were installed directly by the consultant, while fields with other materials only expected information from the internet and did not get clear source information.